Control of Root-knot Nematodes (Meloidogyne spp.) on Tomato (Lycopersicum esculentum Mill.) using Antagonist Fungi - Trizelia Trizelia Trizelia; Winarto Winarto; Rusdi Rusli; Duma Putri Tama; Husnil Barokah; Febriza Yusra Andini (JERAMI : Indonesian Journal of Crop Science, 2023)
Nematodes Meloidogyne spp. is the most important phytonematode in the world, especially in agriculture in tropical areas. The level of root damage to tomato plants caused by the nematode Meloidogyne spp. can reach 68.3%. In general, control of plant parasitic nematodes is still carried out using pesticides in the form of insecticides which can also be used as nematicides. Continuous use of chemicals to control nematodes can cause environmental pollution, resurgence and nematode resistance to chemicals. One alternative control is biological. One of the biological agents that can be used to control Meloidogyne nematodes is the endophytic fungus Beauveria bassiana and Trichoderma asperellum. The research aims to obtain the best isolates of endophytic fungi for controlling rootknot nematodes (Meloidogyne spp.). The isolates tested were 2 Beauveria bassiana isolates and 2 Trichoderma asperellum isolates. The results showed that the fungus isolate Beauveria bassiana isolate TD312 had a higher ability to control Meloidogyne spp on tomatoes.